2018
DOI: 10.1101/324236
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell type specific profiling of alternative translation identifies novel protein isoforms in the mouse brain

Abstract: Translation canonically begins at a single AUG and terminates at the stop codon, generating one protein species per transcript. However, some transcripts may use alternative initiation sites or sustain translation past their stop codon, generating multiple protein isoforms. Through other mechanisms such as alternative splicing, both neurons and glia exhibit remarkable transcriptional diversity, and these other forms of post-transcriptional regulation are impacted by neural activity and disease. Here, using rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 88 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…Though TRAP can provide a proxy for protein levels, protein abundance also depends on the rate of translation and protein degradation. Recently, TRAP was combined with ribosome footprinting, which can define the exact location of a ribosome on the transcript and aides in addressing translation rates and provide an even better proxy for protein levels (Sapkota et al, 2018).…”
Section: Trap: Analysis Of Actively Translated Transcriptsmentioning
confidence: 99%
“…Though TRAP can provide a proxy for protein levels, protein abundance also depends on the rate of translation and protein degradation. Recently, TRAP was combined with ribosome footprinting, which can define the exact location of a ribosome on the transcript and aides in addressing translation rates and provide an even better proxy for protein levels (Sapkota et al, 2018).…”
Section: Trap: Analysis Of Actively Translated Transcriptsmentioning
confidence: 99%
“…We began by evaluating a dual luciferase assay that we have previously used to quantify readthrough (Sapkota et al, 2019) for its suitability as a screening approach. This assay utilizes a dual luciferase vector with an Aqp4 test cassette cloned in between Renilla and Firefly luciferases in such a way that the former is expressed constitutively, but the latter only if the Aqp4 stop codon is read past by ribosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Viruses use stop codon readthrough to increase their protein repertoire from a limited amount of genetic material (Firth and Brierley, 2012). Higher-order organisms, from yeasts to humans, also use a programmed readthrough in a subset of transcripts (Dunn et al, 2013;Loughran et al, 2014;Sapkota et al, 2019). Studies on a few of these transcripts have shown that the C-terminally extended protein variants arising from readthrough can gain new properties (Loughran et al, 2018;Schueren et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations